Angiographic assessment of coronary arteries atherosclerosis of the heart transplant - S. A. Sakhovsky; D. A. Izotov; N. N. Koloskova; I. I. Muminov; R. L. Ahmadzaj; R. A. Faradzhov; E. A. Spirina; V. N. Poptsov; B. L. Mironkov; A. O. Shevchenko (Вестник трансплантологии и искусственных органов, 2019)
Aim. To estimate the frequency and expressiveness of atherosclerotic lesions of the transplant coronary arteries of the determined by an angiographic method.Materials and methods. Coronary angiography was executed to 518 recipients of heart aged from 10 till 72 years (average 56,92 ± 12,1) within the first week after transplantation of heart (a median 6; 3–42 days). Men – 466, women – 52. Initial status of recipients: UNOS 1A – 217 of people, UNOS 1B – 89 of people, UNOS 2 – 212 people. Included the following criteria of the donor in the analysis: sex, age, cause of brain death.Results. Angiographic signs of atherosclerotic lesions of coronary arteries are discovered in 166 cases, in 65 cases defined as significant stenosis which demanded performance of the percutaneous coronary intervention (PCI). In 352 cases symptoms of atherosclerosis are not revealed (group of comparison). At recipients in the status UNOS 1A and UNOS 1B discovered the transmission of atherosclerosis (TA) more often, than recipients in the status UNOS 2 (54% and 36%, respectively). Age of donors in group with transmission of atherosclerosis was 50,2 ± 0,7 years, and in group of comparison – 41 ± 0,6 years (r = 0,0005). Range of donors age in groups did not differ and made 18–66 years for group of comparison and 20–67 years for group with transmission of atherosclerosis, but in subgroup of PCI made 31–67 years. Gender influence on the frequency of transmission of coronary atherosclerosis it is not revealed. Acute violation of brain blood circulation as the cause of brain death was observed in 76% of cases at TA group and 61% in group of comparison.Conclusion. The age of the donor and acute violation of brain blood circulation are the factors associations with probability of transmission of coronary atherosclerosis, however it is important to consider the status of the recipient.